Exploring the effects of good local governance on citizens' trust in Malaysia / Mohd Rozaimy Ridzuan ...[et al.] - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani; Kong, Lai Kuan; Ju, Soon Yew; Yaacob, Nur Ain (Universiti Teknologi MARA, 2021)
Citizens' trust and confidence in politicians and governments at all levels, be it local or national in all countries, has been on the decline for some time. Various studies have revealed that the current widespread public adverse perceptions towards local government are not solely the result of a weak service delivery system but also the absence of a transparent method for public participation and consultation. Therefore, this study seeks to examine the relationship between the elements of good local governance practices (accountability, responsiveness, transparency, and the rule of law) and citizens' trust. A quantitative approach is employed in this study whereby questionnaires had been distributed to residents in the district of Kuantan, Pahang, Malaysia. The study's findings show that the elements of good local governance such as accountability, responsiveness, transparency, and the rule of law are positively associated with citizens' trust. This study is vital as it supplements the existing knowledge on good local governance in the Malaysian Local Government, particularly in Kuantan, Pahang.